Law, territory and conflict resolution : law as a problem and law as a solution - Nicolini, Matteo; Palermo, Francesco; Milano, Enrico (Studies in territorial and cultural diversity governance, 2016)
Prompted by the de facto secession of Crimea in early 2014, Law, Territory and Conflict Resolution explores the role of law in territorial disputes, and therefore sheds light on the legal 'realities' in territorial conflicts. Seventeen scholars with backgrounds in comparative constitutional law and international law critically reflect on the well-established assumption that law is 'part of the solution' in territorial conflicts and ask whether the law cannot equally be 'part of the problem'. The volume examines theory, practice, legislation and jurisprudence from various case studies, thus offering further insights on the following complex issue: can law act as an effective instrument for the governance of territorial disputes and conflicts?